Puborectalis muscle and External Anal Sphincter: a functional unit? - Nikolaos Andromanakos; Dimitrios Filippou; Nikolaos Karandreas; Alkiviadis Kostakis (Turkish Journal of Gastroenterology, 2020)
Cite this article as: Andromanakos N, Filippou D, Karandreas N, Kostakis A. Puborectalis muscle and External Anal Sphincter: a functional unit? Turk J Gastroenterol 2020; 31(4): 342-3.